Identifying the fields of activity, challenges and positive outcomes of nursing prescription: A systematic review - Mahdieh Arian; Monir Nobahar; Nayyereh Raiesdana; Mohammad Bagher Oghazian (Tehran University of Medical Sciences, 2018)
Background & Aim: Nursing prescription is an expanding category with many supporters and critics. The present research attempts to answer three questions: What are the fields of activity of nurse prescribers? What are the challenges of nursing prescription? and what are the positive outcomes of nursing prescription? Methods & Materials: In the present systematic review, all relevant papers published until March 2017, were examined. Search was done in databases: SID, Iran Medex, Iran Doc, Magiran, Science Direct, Medline/PubMed, Web of Science, Scopus, ProQuest, Google Scholar, Cochrane Library and with keywords: nursing prescription, nurse prescribing, nurse prescriber, independent prescribing, supplementary prescribing and their equivalent terms in persian. Inclusion criteria were articles in English or persian, quasi experimental, questionnaire based study, qualitative study and relevant to the objectives of the study. Exclusion criteria were review articles, posters, presentation, and letter to the editor. Results: A total of 72 articles that were included in the systematic review, showed extensive nurse prescribing activity in the fields of diabetes, mental health, rheumatology, dermatology, primary care, elderly care, epilepsy, pain, asthma, hypertension, constipation, emergency, hemodialysis, glaucoma and elderly. Challenges included: the critical look of the care team and lack of support, lack of attention to professional competence assessment, legal constraints, and lack of community awareness of the role of nurse purscribers. The positive outcomes of nursing prescription were classified in three areas related to the patient, the nurse and the organization. Conclusion: Nurse prescribing activity is changing, and identifying its challenges and outcomes will help it progress.